Theoretical elements for a historical approach to the family and its relations of violence during the transition between the XXth and XXIst centuries - García Sánchez, Bárbara Yadira; Guerrero Barón, Javier (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The objective of this article is to relect upon the history of the ield of contemporary family and its changes from the revolution of youth in 1960s until the irst decade of the XXIst century. This historical approach is linked to the study of relations of violence inside the family context. The implementation of certain theoretical and methodological concepts allowed us to establish a contrast between several time periods, starting from the present and going back to situations of the past, following the track of micro social conlicts expressed in violence toward parental igures, as well as in violence between siblings, all of which are analyzed as typologies of what has been called domestic violence. The theoretical relection is supported by some approaches of Pierre Bourdieu regarding the reproduction of symbolic violence, and more speciically, the strategies of its reproduction in the ield of family. We emphasize on the strategies of symbolic, ethicaland educational inversion. The data used to support this article is taken from the database of two research projects on school violence in Bogota between 2009 and 2015.